2016
DOI: 10.5194/gmd-9-2925-2016
|View full text |Cite
|
Sign up to set email alerts
|

Large-eddy simulation and stochastic modeling of Lagrangian particles for footprint determination in the stable boundary layer

Abstract: Large-eddy simulation (LES) and Lagrangian stochastic modeling of passive particle dispersion were applied to the scalar flux footprint determination in the stable atmospheric boundary layer. The sensitivity of the LES results to the spatial resolution and to the parameterizations of small-scale turbulence was investigated. It was shown that the resolved and partially resolved ("subfilter-scale") eddies are mainly responsible for particle dispersion in LES, implying that substantial improvement may be achieved… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 57 publications
0
14
0
3
Order By: Relevance
“…It should also be noted that a targeted refinement in the z direction, while using coarser horizontal resolution in effort to generate thin subvolumes that approximate planes, does not remedy the situation because the mean flow gradients around the sensor site are significant in all directions. Such finite planes or one-cell-high grid layers are conventionally used as targets when Lagrangian-particle-based methods are utilized to evaluate footprints under heterogeneous conditions with undisturbed sensor sites (e.g., Steinfeld et al, 2008;Hellsten et al, 2015;Glazunov et al, 2016). Unfortunately, at the required level of target volume discretization, the excessive number of individual f i,j,k contributions causes the postprocessing to become highly tedious.…”
Section: Coordinate Rotation Via Far-field Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that a targeted refinement in the z direction, while using coarser horizontal resolution in effort to generate thin subvolumes that approximate planes, does not remedy the situation because the mean flow gradients around the sensor site are significant in all directions. Such finite planes or one-cell-high grid layers are conventionally used as targets when Lagrangian-particle-based methods are utilized to evaluate footprints under heterogeneous conditions with undisturbed sensor sites (e.g., Steinfeld et al, 2008;Hellsten et al, 2015;Glazunov et al, 2016). Unfortunately, at the required level of target volume discretization, the excessive number of individual f i,j,k contributions causes the postprocessing to become highly tedious.…”
Section: Coordinate Rotation Via Far-field Correctionmentioning
confidence: 99%
“…The deterministic velocity components are directly obtained from the LES solution, while the random components are evaluated according to Weil et al (2004). Although LS modeling approaches that are less computationally expensive exist (Glazunov et al, 2016), warranting further investigation on their applicability to urban problems, the presented high-resolution urban flow problem is assumed to require the highest level of description also from the LS model; the interaction between the atmospheric wind and the cascade of multistoried buildings and street canyons gives rise to strongly anisotropic turbulence structures, which are not reliably amendable to parametrization.…”
Section: Numerical Modeling Frameworkmentioning
confidence: 99%
“…Increased local knowledge and general understanding of the relevant processes (e.g. Glazunov et al, 2016) can then help the forecasters to improve air quality predictions based on NWP models, as suggested by Steyn et al (2013).…”
mentioning
confidence: 99%
“…The individual sectional footprints are typically evaluated from subsets that contain an insufficient number of particle data entries needed to obtain a converged footprint distribution. (Hellsten et al, 2015) showed that, in an urbanlike environment, ∼ 10 6 particle hits are required to attain an adequately converged footprint distribution while ∼ 10 5 particle entries is sufficient to reveal the characteristic shape of the near-field distribution. In the piecewise postprocessing approach, the sectional footprint contributions may be constructed from an arbitrarily small dataset, but since the methodology substantially benefits from the ability to inspect and compare individual f i,j,k distributions, it is desirable to work with subsets s i,j,k containing more than 10 5 entries.…”
Section: Piecewise Postprocessing Methodology For Constructing the Fomentioning
confidence: 99%
“…It should also be noted that a targeted refinement in the z direction, while using coarser horizontal resolution in effort to generate thin subvolumes that approximate planes, does not remedy the situation because the mean flow gradients around the sensor site are significant in all directions. Such finite planes or one-cell-high grid layers are conventionally used as targets when Lagrangian-particle-based methods are utilized to evaluate footprints under heterogeneous conditions with undisturbed sensor sites (e.g., Steinfeld et al, 2008;Hellsten et al, 2015;Glazunov et al, 2016). Unfortunately, at the required level of target volume discretization, the excessive number of individual f i,j,k contributions causes the postprocessing to become highly tedious.…”
Section: Coordinate Rotation Via Far-field Correctionmentioning
confidence: 99%